2015
DOI: 10.1371/journal.pone.0143555
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Sex Steroids and Anthropometric Markers of Puberty - A Novel Approach to Characterising Within-Person Changes of Puberty Hormones

Abstract: Background/AimsThe longitudinal relationships of within-individual hormone and anthropometric changes during puberty have not ever been fully described. The objectives of this study were to demonstrate that 3 monthly urine collection was feasible in young adolescents and to utilise liquid chromatography-tandem mass spectrometry assay methods for serum and urine testosterone (T), estradiol (E2) and luteinizing hormone (LH) in adolescents by relating temporal changes in urine and serum hormones over 12 months to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Following this, tandem-mass spectrometry analysis was performed using an API-5000 triple-quadrupole mass spectrometer (Applied Biosystem/MDS SCIEX, Ontario, Canada). 6,14 This method can quantify low levels of circulating E 2 and T in 99% of serum specimens from adolescents. 6…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this, tandem-mass spectrometry analysis was performed using an API-5000 triple-quadrupole mass spectrometer (Applied Biosystem/MDS SCIEX, Ontario, Canada). 6,14 This method can quantify low levels of circulating E 2 and T in 99% of serum specimens from adolescents. 6…”
Section: Methodsmentioning
confidence: 99%
“…Early morning serum E 2 (collected in follicular phase for post-menarcheal participants) and T were measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS) using previously described methods. 6,14 Briefly, organic solvent extracts of serum were separated by liquid chromatography using a Shimadzu Nexera UHPLC system (Shimadzu Scientific Instruments, Columbia, MD). Following this, tandem-mass spectrometry analysis was performed using an API-5000 triple-quadrupole mass spectrometer (Applied Biosystem/MDS SCIEX, Ontario, Canada).…”
Section: Hormone Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study examining the correlation of three-monthly urinary oestradiol, testosterone and LH with self-reported SMS-based Tanner staging, the levels of all three hormones were correlated with the staging at baseline and 12 months later. 43 In another study, staging based on physical examination reflected testosterone and DHEA levels in both sexes, but was only modestly related to oestradiol in girls. 44 In boys, 24-hour testosterone levels in later puberty correlate reasonably well with testicular volume.…”
Section: Hormonal Assessmentmentioning
confidence: 95%
“…45 However, assays of urinary sex hormones both in boys and girls can be difficult to interpret due to within-person variability, and longitudinal sampling would be required to determine the hormonal changes associated with progression through pubertal stages. 43,46 It has been suggested that both inhibin A and B may have a potential as markers of pubertal development in boys and girls. 46,47 However, progressive changes in their levels are not consistent enough to enable pubertal staging.…”
Section: Hormonal Assessmentmentioning
confidence: 99%